Analisis Terhadap Pelaksanaan Izin Lingkungan Reklamasi Pantai Manakkara Mamuju - Muhammad Al Habsy Ahmad; Ina Marselina (Jurnal Litigasi Amsir, 2022)
Reclamation is a form of human intervention in the balance of the natural environment which is always in a state of dynamic balance. This change gives birth to ecosystem changes such as changes in current patterns, erosion and coastal sedimentation which have the potential to increase the risk of flooding. This study aimed to obtain an overview of the procedure for issuing an environmental permit for the reclamation of the Manakarra Mamuju beach and the mechanism for implementing the environmental permit for reclamation in the coastal area of Manakarra Mamuju according to Law Number 32 of 2009 concerning Environmental Protection and Management. This research was conducted in Mamuju Regency. The data collection method used is the library method, and the interview method then the data obtained is analyzed qualitatively and then presented in a descriptive normative manner, namely explaining, describing, and drawing conclusions on the problem. Based on the results of the study it was found that 1. The issuance of the environmental permit for the reclamation of the Manakarra Mamuju beach was not in accordance with Law no. 32 of 2009 concerning Environmental Protection and Management (PPLH). 2. The implementation of the environmental permit for reclamation in the coastal area of Manakarra Mamuju, is not and/or has not been effective as stipulated in the laws and regulations.